(untitled) (Journal of Fiber Bioengineering and Informatics, 2013)
The structure of carriers play an important role in the space distribution of different drugs, therefore this paper studies multivesicular liposomes (MVLs), which have a unique nano-in-micro structure as possible carriers in combination therapy. Horseradish peroxidase (HRP) and mitoxantrone hydrochloride (DHAD) were selected as model drugs for protein and small molecule drug respectively. The results show that the MVLs are spherical and that the internal space is divided up into numerous compartments. The particle size ranged from 15 to 20 μm and the system was stable according to the zeta potentials. In vitro release studies display that the DHAD/HRP co-loaded MVLs has better sustained release profiles than one drug alone, and the MVLs exhibited an orderly release behavior which suggested that MVLs might be used as drug carriers in combination therapy applications.